The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1974
DOI: 10.1128/iai.9.1.44-47.1974
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Purified Proteins and Polysaccharides from Mycobacterium tuberculosis in Delayed Skin Test and Cultured Lymphocyte Mitogenesis Assays

Abstract: Hypersensitivity responses to two highly purified and well characterized mycobacterial proteins and a preparation of mycobacterial arabinogalactanarabinomannan were studied by using guinea pig skin tests and in vitro-cultured human lymphocyte mitogenesis stimulation assays. The purified proteins were found to elicit delayed-type hypersensitivity skin test reactions and to stimulate mitogenesis in cultured lymphocytes. The polysaccharide preparation was found to evoke delayed skin tests but not to stimulate cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1975
1975
1995
1995

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…It seems possible that some mycobacterial polysaccharides may have distinctive antigenic properties that cause them to react differently in different hosts, under differing conditions of immunization, or in different assay systems. This is probably not true for proteincontaining fractions (60,103), and a close correlation between delayed skin test reactions and lymphocyte mitogenesis has been demonstrated with PPD in healthy tuberculin-positive persons (106, 128) and in patients with tuberculosis (94,110). However, these antigenic dichotomies are not necessarily restricted to mycobacterial polysaccharide antigens.…”
mentioning
confidence: 99%
“…It seems possible that some mycobacterial polysaccharides may have distinctive antigenic properties that cause them to react differently in different hosts, under differing conditions of immunization, or in different assay systems. This is probably not true for proteincontaining fractions (60,103), and a close correlation between delayed skin test reactions and lymphocyte mitogenesis has been demonstrated with PPD in healthy tuberculin-positive persons (106, 128) and in patients with tuberculosis (94,110). However, these antigenic dichotomies are not necessarily restricted to mycobacterial polysaccharide antigens.…”
mentioning
confidence: 99%
“…We have not ruled out the possibility that lipopolysaccharide comigrating with the 35-kDa protein contributes to the observed T-cell response to the MLP fraction. However, other investigators (5,6,17,33), as well as our group (Mohagheghpour, unpublished data), have failed to detect any T-cell responses to mycobacterium-derived lipopolysaccharides, including lipoarabinomannan B of M. leprae. Moreover, previous studies have demonstrated that lipoarabinomannan B nonspecifically inhibits T-cell reactions (6,17).…”
Section: Discussionmentioning
confidence: 76%
“…Peptides and proteins of intracellular bacteria are considered responsible for the delayed-type hypersensitivity of cell-mediated immunity (DANIEL and HINZ, 1974;JONES and BERMAN, 1975). Although various methods have been used to prepare allergens (LIVE and STUBBS, 1947;OTTOSEN and PLUM, 1949;PARNAS et al, 1966;BHONGBHIBHAT et al.…”
Section: Introductionmentioning
confidence: 99%